Does hearing loss relate to gestational diabetes mellitus? - Kwatra, Devanshu; Kumar, Sunil; Singh, Gautam Bir; Biswas, Ratna; Upadhyay, Prabhakar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: This study aims to check if gestational diabetes mellitus leads to changes in hearing. Methods: A prospective hospital based observational study was performed with total 60 subjects in age group of 18-40 years in the Department of Otolaryngology and Head and Neck Surgery and the Department of Obstetrics and Gynaecology, Lady Hardinge Medical College, New Delhi between November 2016 to March 2018. Subjects were divided in two groups. The first group included 30 pregnant women with diagnosed gestational diabetes mellitus and the second group had 30 pregnant women not having gestational diabetes mellitus. Pure-tone audiometry and impedance audiometry was performed twice in all the subjects, first during the antepartum period and second time during the postpartum period. Results: Significant difference was seen between the average of air conduction threshold values at speech frequencies between the two groups during both antepartum and postpartum period. Conclusions: The alterations in hearing sensitivity in air conduction between the two groups can be attributed to gestational diabetes mellitus.